Analisis Forensik terhadap Tahapan Pembusukan sebagai Indikator Post-Mortem Interval: Tinjauan Pustaka - Zahra Dewi Hasna Difa; Anggela; Septia Eva Lusina (Medula, 2026)
Decomposition is a complex biological process that occurs after death as a result of the interaction between autolysis, microbial activity, and environmental influences. In forensic medicine, the analysis of decomposition stages plays an important role in estimating the post-mortem interval (PMI), particularly in cases of unnatural death and advanced body decomposition. Open wounds and traumatic injuries are known to accelerate decomposition due to increased microbial exposure and insect activity within body tissues. This literature review aims to discuss the physiological and morphological mechanisms of decomposition, factors affecting the rate of body degradation, and recent advances in modern approaches for PMI estimation. The study was conducted using a literature review method through article searches in PubMed, ScienceDirect, and Google Scholar databases using the keywords “forensic”, “decomposition”, “medicolegal”, “thanatology”, and “post-mortem interval”. The included literature consisted of national and international articles published between 2020 and 2025, along with several major forensic medicine textbooks. The review demonstrated that decomposition begins with the failure of cellular homeostasis, leading to tissue autolysis followed by putrefaction caused by microbial activity. The rate of decomposition is influenced by several factors, including environmental temperature, humidity, body location, insect activity, body mass, and the presence of open wounds. Multidisciplinary approaches integrating morphological observation, histopathology, forensic entomology, thanatomicrobiome analysis, and molecular biomarkers have been shown to improve the accuracy of PMI estimation compared to the use of a single method. Therefore, understanding the stages of decomposition and the factors influencing them is essential in supporting medical and criminal investigations as well as improving the accuracy of post-mortem interval interpretation.